Figure 1 from: Pezzani R (2016) Saxifraga aizoides extract: novel potential effects on tumor cell models. Research Ideas and Outcomes 2: e9632. https://doi.org/10.3897/rio.2.e9632 - Pezzani, Raffaele (Zenodo, 2016)
Figure 1 - Saxifraga aizoides is a flowering herb of the genus Saxifraga, which lives in Europe and North America.